# Simplify the following: (√3 - √2)²

**Solution:**

Given, the expression is (√3 - √2)²

We have to simplify the expression.

Using the algebraic identity,

(a - b)² = a² - 2ab + b²

(√3 - √2)² = (√3)² - 2√3√2 + (√2)²

= 3 - 2√6 + 2

= 5 - 2√6

Therefore, (√3 - √2)² = 5 - 2√6

**✦ Try This: **Simplify the expression: Simplify the following: (√5 + √3)²

Given, the expression is (√5 + √3)²

We have to simplify the expression.

Using the algebraic identity,

(a + b)² = a² + 2ab + b²

(√5 + √3)² = (√5)² + 2√5√3 + (√3)²

= 5 + 2√15 + 3

= 8 + 2√15

Therefore, (√5 + √3)² = 8 + 2√15

**☛ Also Check: **NCERT Solutions for Class 9 Maths Chapter 1

**NCERT Exemplar Class 9 Maths Exercise 1.3 Problem 9(vi)**

## Simplify the following: (√3 - √2)²

**Summary:**

Irrational numbers are the set of real numbers that cannot be expressed in the form of a fraction, p/q where p and q are integers. The simplified form of (√3 - √2)² is 5 - 2√6

**☛ Related Questions:**

visual curriculum